DAMPAK LINGKUNGAN KERJA DAN PRESTASI KERJA TERHADAP EFEKTIVITAS PELAYANAN PADA DINAS PENDIDIKAN KOTA SOLOK - Esi Sriyanti; Wahyu Indah Mursalini; Arfimasri Arfimasri; Serly Rama Yanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study was conducted at the Solok City Education Office to determine the impact of the work environment and work performance on service effectiveness. The study population consisted of 96 employees at the Solok City Education Office, with a sample of 50 individual’s selected using purposive sampling. Data collection was carried out via questionnaires. Substantively, the findings indicate that both the work environment and work performance have a positive and significant influence on service effectiveness at the Solok City Education Office, whether analyzed individually or simultaneously. Consequently, agency leadership should formulate policies focused on enhancing employee performance through competency training programs, clear work targets, and rewards for high-performing staff. The study's limitations include the use of a non-probability sampling method (purposive sampling) and a relatively small sample size, necessitating caution when generalizing the results. Furthermore, the study was limited to two independent variables, whereas public service effectiveness is also influenced by factors such as digital technology adoption, leadership style, and organizational culture—none of which were included in this research model.